Just What Are They Reading? Exploring Text in Video Games - Camm, Sarah C.; Whippey, Caroline (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
While recent literature has explored video games, literacy, and education, little attention has been paid to the actual text found in video games. This study examines five popular video games, exploring the purpose of the text, how it is presented, and how appropriate the text is for the intended audience. Récemment, la littérature a exploré les jeux vidéo, la maîtrise de l’information et l’éducation, mais peu a été consacré au texte contenu dans les jeux vidéo. Cette étude examine cinq jeux vidéo populaires et explore l’objectif du texte, sa présentation et la pertinence du texte pour le public ciblé.